The effect of different solutions in tracheal suctioning on the incidence of pneumonia in patients on the ventilator - Chai, Chunyan; Liu, Xiangzeng; Zhao, Yuan (Cellular and Molecular Biology, 2022)
Ventilator-associated pneumonia (VAP) is a common nosocomial infection in patients admitted to intensive care units (ICU), leading to prolonged stay in the ICU, increased hospital costs, and mortality. This study aimed to compare the effect of using normal saline with eucalyptus in endotracheal suctioning on the rate of ventilator-dependent pneumonia. For this purpose, a randomized clinical trial study was performed on 120 patients under a ventilator in the hospital ICU. Patients were randomly divided into control and intervention groups. The control group consisted of 60 patients who used 0.9% normal saline to dilute endotracheal secretions. The intervention group also included 60 patients treated with 0.9% normal saline with 5% eucalyptus to dilute endotracheal secretions. The sensitivity of isolated microbes was determined by the diffusion susceptibility test Kirby-Bauer disk protocol. The CDC protocol was used to diagnose VAP. 100 CFU/ml of endotracheal aspiration was considered the differentiation number between the microbe responsible for VAP and colonization. Whenever a VAP guess was made, a blood culture was done. Finally, the incidence of ventilator-associated pneumonia in the two groups was compared. The results showed that the incidence of VAP during using normal saline and normal saline with eucalyptus as a diluent for pulmonary secretions was different between the two groups (P = 0.042). Also, among infected patients with VAP, there was a difference between the types of microorganisms in the two groups (P = 0.019). Seven cases of Klebsiella pneumonia were observed in the control group, while no case of this bacterium was observed in the intervention group. In terms of the prevalence of Pseudomonas (two cases), both groups had a similar situation. These findings can reassure nurses and the treatment team that they can use normal saline solution with 5% eucalyptus during suction to dilute pulmonary secretions.